Coal and Blood: Industrialization and the Rise of Nationalism in Prussia before 1914 - Felix Kersting (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Industrialization and the rise of nationalism were the two major developments in Germany before the World War I. A novel county-level dataset reveals that industrialization and nationalism measured by membership in the K̈riegervereine\'\", the biggest civil organization at the time, were negatively correlated. Using coal potential as an IV for identification, I find strong evidence for a causal impact of industrialization on nationalism. In order to detect possible mechanisms, a three stage IV regression model produces strong support that migration and trade union membership were crucial factors that linked industrialization and nationalism.
Keywords: F06; N13; N33; 330; nationalism; industrialization; prussia